The natural history of acromial stress fracture after reverse total shoulder arthroplasty. Issue 4 (July 2018) - Merlin, Gabriel; Louise Fowler, Mary; Dashe, Jesse; Smiley, Paul; Lemos, Mark
Abstract : Background: The purpose of our study was to observe the natural history of acromial stress fracture after reverse total shoulder arthroplasty. Methods: In a two-surgeon, single academic institution, seven patients with acromial fractures after reverse total shoulder arthroplasty were identified and evaluated for pain and functional outcome based on a visual analog scale (VAS), Disability of the Arm, Shoulder, and Hand (DASH) score, and range of motion to compare with results after uncomplicated reverse total shoulder arthroplasty. Outcomes of the acromial stress fracture group were broken down by Levy classification. Results: There was no significant difference in VAS, DASH score, or range of motion between Levy 1 and 2 and uncomplicated reverse total shoulder arthroplasty. Levy 3 had significantly decreased forward flexion compared with Levy 1 and 2. Multivariate logistic regression did not show any association between fracture and smoking status, hand dominance, gender, or age. Levy 3 acromial fractures fared worse in this series than the other fracture types, eventually requiring open reduction internal fixation. Conclusions: The natural history of patients after reverse total shoulder arthroplasty with an acromial fracture is similar to patients without acromial fracture regarding pain and function on a DASH score. Nonoperative treatment should be attempted for Levy 1 and Levy 2 acromial fractures before offering the patient operative treatment after reverse total shoulder arthroplasty. Levy 3 fractures potentially need operative fixation. Multicenter, prospective studies should be carried out to increase the sample size of patients with acromial stress fracture after reverse total shoulder arthroplasty to assess long-term outcome. Level of Evidence: Level III, therapeutic study.